2012
DOI: 10.4048/jbc.2012.15.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Internal Mammary Lymph Node Detected by Lymphoscintigraphy in Early Breast Cancer

Abstract: PurposeInternal mammary lymph node (IMLN) metastasis is an important prognostic indicator in breast cancer. However, the necessity of internal mammary sentinel lymph node biopsy for accurate staging, for choosing adjuvant treatment, and as a prognostic indicator, has remained controversial.MethodsFrom January 2001 to December 2006, 525 female breast cancer patients underwent radical surgery after preoperative lymphatic scintigraphy. We retrospectively analyzed the follow-up results, recurrences, and deaths of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In addition, the survival benefit afforded by surgical excision of internal mammary lymph nodes has not been conclusively shown [6,26]. Because the benefit is unclear and potential complications surround internal mammary node excision, most internal mammary lymph node metastasis patients are treated with adjuvant chemotherapy or radiation rather than surgical dissection [27].…”
Section: Mri Of Internal Mammary Lymph Nodesmentioning
confidence: 99%
“…In addition, the survival benefit afforded by surgical excision of internal mammary lymph nodes has not been conclusively shown [6,26]. Because the benefit is unclear and potential complications surround internal mammary node excision, most internal mammary lymph node metastasis patients are treated with adjuvant chemotherapy or radiation rather than surgical dissection [27].…”
Section: Mri Of Internal Mammary Lymph Nodesmentioning
confidence: 99%
“…However, no statistically significant difference was found for overall survival (OS; 78% versus 64%; P=0.08). No overall survival differences were reported either by Koo et al 49 , Fisher et al 50 , and Arriagada et al 51 . Overall survival and disease free survival are summarized in Tables 2 and 3.…”
Section: Management Of Imn and Impact On Disease-free And Overall Patmentioning
confidence: 65%
“…Koo et al on the other hand states that internal mammary SLNB (IMSLNB) can be omitted in early breast cancer. In a study concerning 525 patients', he demonstrated no significant difference in survival outcomes of those who did and those who did not have IMSLNB [20]. According to Birdwell et al, scintigrams are not mandatory especially if internal mammary node status is not acted upon [18].…”
Section: Discussionmentioning
confidence: 97%